Preparation method of flame-retardant, light-emitting and recoverable transparent polyurethane material
By preparing a combination of luminescent flame retardant and polyurethane material, the problems of flammability and environmental pollution of polyurethane materials are solved, and efficient flame retardant, photoluminescence and recyclability are achieved, improving the photoelectric conversion efficiency of flexible solar cells and ensuring safety.
Patent Information
- Application Number
- CN202510410859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
Existing polyurethane materials are flammable and difficult to ensure safety. In addition, traditional halogen-containing flame retardants have environmental pollution problems, so it is necessary to develop environmentally friendly, halogen-free flame retardant polyurethane materials. At the same time, the photoelectric conversion efficiency of flexible solar cells is low, and it is necessary to improve the power generation efficiency of materials.
The luminescent flame retardant is prepared by reacting triethanolamine with diphenylphosphonochloride and polymerized with polyether polyol, isocyanate and chain extender to prepare a transparent polyurethane material with flame retardant, luminescent and recyclable properties.
It realizes the efficient flame retardant, photoluminescence and recyclability of polyurethane materials, improves the photoelectric conversion efficiency of flexible solar cells, and ensures the fire safety of the materials.
Smart Images

Figure CN119912660A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials and relates to a method for preparing a transparent polyurethane material with flame retardancy, luminescence and recyclability. Background Art
[0002] Thermoplastic polyurethane elastomer is a block copolymer composed of soft segments and hard segments. It combines many advantages such as high elasticity, low temperature resistance, corrosion resistance, and wear resistance. It is widely used in transportation, electronic equipment, architectural decoration and other fields. However, its application scenarios are often limited by its own defects. Pure polyurethane is a flammable material, which often makes it impossible to guarantee its safety during actual application, posing a hidden danger to the safety of human life and property. Therefore, the flame retardant modification of polyurethane materials has become particularly urgent. From the development history of polyurethane flame retardants, although halogen-containing flame retardants have excellent performance, they will produce a large amount of corrosive and toxic gases during the combustion process, which is seriously inconsistent with the current green and environmental protection development concept, and has therefore been abandoned by people.
[0003] At present, the development of more environmentally friendly, halogen-free flame-retardant polyurethane materials has become a top priority. Among the many flame retardants, nitrogen-phosphorus-based synergistic flame retardants have attracted much attention due to their excellent flame retardant properties, high flame retardant efficiency, less smoke generation, and low toxicity. They are expected to provide the polyurethane material industry with more environmentally friendly, safe, and efficient flame retardants. In addition, expanding the actual application scenarios of polyurethane materials and achieving multifunctional development is a major trend. The solar energy industry is a highly promising clean energy field, and solar cell encapsulation is one of the ideal application scenarios for polyurethane elastomers. Flexible solar cells, as a promising material, have also been the focus of attention. However, despite the many advantages of flexible solar cells, the problem of low photoelectric conversion efficiency always exists. Therefore, improving the power generation efficiency of flexible solar cells has become a research focus for technicians in this field.
[0004] Based on this, the present invention aims to provide a polyurethane material with flame retardancy, luminescence, high tensile strength and recyclability, which can be applied to flexible solar cells to improve the photoelectric conversion efficiency of the flexible solar cells. Summary of the invention
[0005] In view of the above technical problems, the present invention aims to provide a method for preparing a flame-retardant, luminescent and recyclable transparent polyurethane material. The transparent polyurethane material is obtained by reacting triethanolamine with diphenylphosphonic chloride to obtain a luminescent flame retardant, and then polymerizing it with polyether polyol, isocyanate and a chain extender. The preparation method of the present invention is simple and the process is easy to control. The prepared transparent polyurethane material can maintain a high tensile strength, and the limiting oxygen index can reach 30.3 and the UL-94 grade can reach V-0, and it has a good flame retardant effect. In addition, due to its high transparency and fluorescence, it can be used as a light transfer film on flexible solar cells, thereby improving the photoelectric conversion efficiency of flexible solar cells.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a flame-retardant, luminous and recyclable transparent polyurethane material is carried out in the following steps: S1. Preparation of luminescent flame retardant Triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and triethanolamine was added and stirred for 30 min, followed by dropwise addition of diphenylphosphonyl chloride and stirring for 3-5 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed 2-4 times with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure and purification by column chromatography to obtain a luminescent flame retardant (NEDP); S2. Preparation of transparent polyurethane material Add polyether polyol into a three-necked flask and heat it to 120°C, then evacuate the glass container and fill it with argon, cool the system to 80°C, add polyisocyanate and stir for 1 h, then lower the temperature to 55°C, add luminescent flame retardant and chain extender, stir for 1-2 min, add 0.6 mL triethylamine to obtain a polymer emulsion, pour it into a polytetrafluoroethylene mold, react and cure in an 80°C oven for 48 h to obtain a transparent polyurethane material.
[0007] As a limitation of the preparation method of the present invention, in step S1, the molar ratio of triethylamine, triethanolamine and diphenylphosphonyl chloride is 5:1:3.
[0008] As another limitation of the preparation method of the present invention, in step S1, the dropping rate of the diphenylphosphonyl chloride is 0.5-0.6 mL / min.
[0009] The dropping rate of diphenylphosphonyl chloride in the present invention is crucial for preparing the luminescent flame retardant. When the dropping rate of diphenylphosphonyl chloride is 0.5-0.6 mL / min, the reaction process will be more stable, so that the reaction will be more fully carried out; however, when the dropping rate is greater than 0.5-0.6 mL / min, the reaction rate will be too fast, resulting in insufficient reaction; when the dropping rate is less than 0.5-0.6 mL / min, the test process will be prolonged, thereby reducing the efficiency, which is not conducive to actual production and experiments.
[0010] As a third limitation of the preparation method of the present invention, in step S2, the molecular weight of the polyether polyol is 1000-3000.
[0011] As the fourth limitation of the preparation method of the present invention, in step S2, the isocyanate is any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexylmethylene diisocyanate, xylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and dimer acid diisocyanate.
[0012] As a fifth limitation of the preparation method of the present invention, in step S2, the molar ratio of the polyether polyol to the isocyanate, the luminescent flame retardant, and the chain extender is 10:20:(3-12):10.
[0013] As a sixth limitation of the preparation method of the present invention, in step S2, the chain extender is obtained by adding 0.9 g of 1,4-butanediol to 2 mL of N,N-dimethylformamide.
[0014] The present invention also has a limitation that in step S1, the structural formula of the luminescent flame retardant prepared is:
[0015] The transparent polyurethane material prepared by the present invention can achieve efficient flame retardancy only through the luminescent flame retardant, which is mainly determined by the nitrogen-phosphorus synergistic mechanism possessed by the luminescent flame retardant. First, the phosphorus-containing free radicals generated by the decomposition of the luminescent flame retardant can capture free free radicals in the air, thereby quenching the flame and achieving the purpose of terminating combustion, and the decomposition of nitrogen elements to produce non-combustible gases such as N2 and NH3 dilutes the concentration of combustible gases around the flame, and also achieves a certain flame retardant effect; secondly, the phosphorus-based groups form phosphates and metaphosphates after capturing free radicals. The substances, which cover the surface of the polyurethane matrix, repair and thicken the carbon layer structure, make the carbon layer dense and crack-free, thereby well isolating the heat transfer and further contact of the combustible gas, thereby achieving efficient flame retardancy. Therefore, the luminescent flame retardant improves the flame retardant effect through the gas phase and the condensed phase.
[0016] The present invention also provides an application of a transparent polyurethane material. The prepared transparent polyurethane material can be used as a light transfer film on a flexible solar cell.
[0017] The polyurethane material prepared by the present invention has high elasticity, high flame retardancy, strong photoluminescence characteristics, recyclability and transparency. The synthesis of the luminescent flame retardant (NEDP) is key in the synthesis process of the material. It is composed of multiple rotatable benzene ring structures and contains nitrogen and phosphorus elements, which ensures that it can be effectively flame-retarded by the cooperation of nitrogen and phosphorus elements, and the benzene rings are restricted from rotating due to aggregation, thereby triggering the photoluminescence effect. The luminescence principle of the luminescent flame retardant is due to the AIE mechanism. Most AIE fluorescent molecules have highly twisted propeller-like structures, indicating that the twisted structure plays a vital role in the AIE phenomenon. When dispersed, the AIE molecules rotate and vibrate rapidly, resulting in a high non-radiative decay rate, so the fluorescence is quenched. When the AIE molecules are aggregated or in a solid state, the molecular conformation is highly distorted, the intermolecular π-π stacking, and the intramolecular motion are restricted, thereby suppressing the non-radiative decay rate. At this time, the radiative decay rate competes with the non-radiative decay rate, thereby increasing the emission quantum yield and emitting a fluorescent effect. Moreover, after adding NEDP, the excellent physical properties of polyurethane such as high elasticity and high tensile strength are not affected, and the recyclability of thermoplastic polyurethane is also well maintained. This is because firstly, the amount of NEDP introduced is small, so the impact on polyurethane is small; secondly, NEDP is a synthetic small molecule structure and does not have groups such as hydroxyl and amino groups that react with polyurethane, so it does not react with polyurethane segments. Other non-reactive flame retardants are inorganic additives with large particle sizes, so they destroy the structure of polyurethane and cause a serious decline in mechanical properties. And because NEDP is a small molecule, the segment sequence of polyurethane itself remains intact, and NEDP exists in the gaps of the polyurethane segment structure, so that polyurethane maintains good mechanical properties, thus well ensuring the needs of practical applications. In addition, the excellent light transmittance of polyurethane materials is the key to their application in flexible solar cells. High light transmittance ensures that it will not affect the normal visible light absorption of solar cells. And due to the fluorescent properties of polyurethane materials, it can absorb ultraviolet light with extremely low utilization rate of solar cells and emit visible blue fluorescence, which just converts the light that solar cells cannot absorb into absorbable light, thereby further improving the intensity of light absorbed by solar cells, thereby achieving an improvement in the photoelectric conversion efficiency of solar cells. Combined with the high elasticity and flexibility of this material, it is a clever application for flexible solar cells, and its excellent flame retardancy further ensures the fire safety of battery use.
[0018] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0019] The above technical solution has the following advantages or beneficial effects: 1. The transparent polyurethane material prepared by the present invention has high tensile strength, excellent flame retardancy, photoluminescence, very few droplets, high transparency and recyclability, and can be used as a light transfer film on flexible solar cells, thereby improving the photoelectric conversion efficiency of flexible solar cells; 2. The preparation method of the present invention is simple, the process is easy to control, the preparation cycle is short, the cost is low, and it is suitable for large-scale industrial production; 3. The transparent polyurethane material prepared by the present invention has a tensile strength of more than 25 MPa, a limiting oxygen index of 30.3, and a UL-94 grade of V-0, and has a good flame retardant effect.
[0020] The invention is suitable for preparing a transparent polyurethane material with flame retardancy, luminescence and recyclability.
[0021] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The structural representation diagram of the luminescent flame retardant prepared in step S1 of Example 1 of the present invention, wherein: (a) is a hydrogen nuclear magnetic resonance spectrum, and (b) is a Fourier transform infrared spectrum; Figure 2 This is the infrared spectrum of the transparent polyurethane material prepared in Examples 1-4 of the present invention; Figure 3 The flame retardant performance characterization diagrams of the transparent polyurethane materials prepared in Examples 1-4 of the present invention, wherein: (a) is a LOI test diagram, (b) is a UL-94 test diagram, and (c) is a LOI and UL-94 evaluation diagram; Figure 4 The mechanical properties diagram of the transparent polyurethane material prepared in Examples 1-4 of the present invention; Figure 5 This is a graph of the ultraviolet transmittance of the transparent polyurethane material prepared in Examples 1-4 of the present invention; Figure 6 The carbon layers of the transparent polyurethane material and pure polyurethane material after combustion prepared in Example 1 of the present invention are characterized by scanning electron microscope images, wherein: (a1) is a 50 micron scanning electron microscope image of the carbon layer of pure polyurethane after combustion, (a2) is a 50 micron scanning electron microscope image of the carbon layer of the transparent polyurethane prepared in Example 1 after combustion, (b1) is a 2 micron scanning electron microscope image of the carbon layer of pure polyurethane after combustion, and (b2) is a 2 micron scanning electron microscope image of the carbon layer of the transparent polyurethane prepared in Example 1 after combustion; Figure 7The recyclable performance characterization diagram of the transparent polyurethane material prepared in Example 1 of the present invention, wherein: (a) is a recycling process diagram, and (b) is a mechanical performance diagram; Figure 8 This is a characterization diagram of the luminescence performance of the polyurethane materials prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0023] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0024] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Embodiment 1
[0025] This embodiment prepares a transparent polyurethane material, and its preparation process and steps are as follows: S1. Preparation of luminescent flame retardant 5 mol of triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and then 1 mol of triethanolamine was added and stirred for 30 min, followed by dropwise addition of 3 mol of diphenylphosphonyl chloride (the dropping rate of diphenylphosphonyl chloride was 0.5 mL / min), and stirred for 3 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed twice with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure, and purification by column chromatography to obtain a luminescent flame retardant; S2. Preparation of transparent polyurethane material 10 mol of polyether polyol was added into a glass container and heated to 120°C. The glass container was then evacuated and filled with argon. The system was cooled to 80°C. 20 mol of hexamethylene diisocyanate was added and stirred for 1 h. The temperature was then lowered to 55°C. 9 mol of luminescent flame retardant and 10 mol of chain extender (prepared by adding 0.9 g of 1,4-butanediol to 2 mL of N,N-dimethylformamide) were added. The mixture was stirred for 1 min. 0.6 mL of triethylamine was added to obtain a polymer emulsion. The emulsion was poured into a polytetrafluoroethylene mold and reacted and cured in an oven at 80°C for 48 h to obtain a transparent polyurethane material. Embodiment 2
[0026] This embodiment prepares a transparent polyurethane material, and its preparation process and steps are as follows: S1. Preparation of luminescent flame retardant 5 mol of triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and then 1 mol of triethanolamine was added and stirred for 30 min, followed by dropwise addition of 3 mol of diphenylphosphonyl chloride (the dropping rate of diphenylphosphonyl chloride was 0.55 mL / min), and stirred for 4 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed 3 times with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure, and purification by column chromatography to obtain a luminescent flame retardant; S2. Preparation of transparent polyurethane material 10 mol of polyether polyol was added into a glass container and heated to 120°C. The glass container was then evacuated and filled with argon. The system was cooled to 80°C. 20 mol of hexamethylene diisocyanate was added and stirred for 1 h. The temperature was then lowered to 55°C. 3 mol of luminescent flame retardant and 10 mol of chain extender (prepared by adding 0.9 g of 1,4-butanediol to 2 mL of N,N-dimethylformamide) were added. The mixture was stirred for 1.5 min. 0.6 mL of triethylamine was added to obtain a polymer emulsion. The emulsion was poured into a polytetrafluoroethylene mold and reacted and cured in an oven at 80°C for 48 h to obtain a transparent polyurethane material. Embodiment 3
[0027] This embodiment prepares a transparent polyurethane material, and its preparation process and steps are as follows: S1. Preparation of luminescent flame retardant 5 mol of triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and then 1 mol of triethanolamine was added and stirred for 30 min, followed by dropwise addition of 3 mol of diphenylphosphonyl chloride (the dropping rate of diphenylphosphonyl chloride was 0.6 mL / min), and stirred for 5 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed 4 times with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure, and purification by column chromatography to obtain a luminescent flame retardant; S2. Preparation of transparent polyurethane material 10 mol of polyether polyol was added into a glass container and heated to 120°C. The glass container was then evacuated and filled with argon. The system was cooled to 80°C. 20 mol of hexamethylene diisocyanate was added and stirred for 1 h. The temperature was then lowered to 55°C. 6 mol of luminescent flame retardant and 10 mol of chain extender (prepared by adding 0.9 g of 1,4-butanediol to 2 mL of N,N-dimethylformamide) were added. The mixture was stirred for 2 min. 0.6 mL of triethylamine was added to obtain a polymer emulsion. The emulsion was poured into a polytetrafluoroethylene mold and reacted and cured in an oven at 80°C for 48 h to obtain a transparent polyurethane material. Embodiment 4
[0028] This embodiment prepares a transparent polyurethane material, and its preparation process and steps are as follows: S1. Preparation of luminescent flame retardant 5 mol of triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and then 1 mol of triethanolamine was added and stirred for 30 min, followed by dropwise addition of 3 mol of diphenylphosphonyl chloride (the dropping rate of diphenylphosphonyl chloride was 0.5 mL / min), and stirred for 3 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed twice with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure, and purification by column chromatography to obtain a luminescent flame retardant; S2. Preparation of transparent polyurethane material 10 mol of polyether polyol was added to a glass container and heated to 120°C. The glass container was then evacuated and filled with argon. The system was cooled to 80°C. 20 mol of hexamethylene diisocyanate was added and stirred for 1 h. The temperature was then lowered to 55°C. 12 mol of luminescent flame retardant and 10 mol of chain extender (prepared by adding 0.9 g of 1,4-butanediol to 2 mL of N,N-dimethylformamide) were added. The mixture was stirred for 1 min. 0.6 mL of triethylamine was added to obtain a polymer emulsion. The emulsion was poured into a polytetrafluoroethylene mold and reacted and cured in an oven at 80°C for 48 h to obtain a transparent polyurethane material. Comparative Example
[0029] In order to explore the effects of different parameters in the preparation process of the present invention or on the performance of the product of the present invention, the following comparative experiments were conducted. Different polyurethane materials were prepared in the following comparative examples, as follows: Comparative Example 1 In this comparative example, a polyurethane material is prepared. The preparation process is similar to that of Example 1, except that in step S1, the molar ratio of triethylamine, triethanolamine and diphenylphosphonyl chloride is 5:2:3.
[0030] Comparative Example 2 In this comparative example, a polyurethane material is prepared. The preparation process is similar to that of Example 1, except that in step S1, the dropping rate of diphenylphosphonyl chloride is 1 mL / min.
[0031] Comparative Example 3 In this comparative example, a polyurethane material is prepared. The preparation process is similar to that of Example 1, except that in step S2, the molar ratio of polyether polyol to hexamethylene diisocyanate, luminescent flame retardant, and chain extender is 1:4:3:3. Performance Testing
[0032] The performance of the polyurethane materials prepared in the examples of the present invention and the comparative examples was characterized as follows: like Figure 1 , which is a structural characterization diagram of the luminescent flame retardant prepared in step S1 of Example 1 of the present invention, wherein (a) is a hydrogen nuclear magnetic resonance spectrum. From Figure (a), it can be seen that the chemical shift at 7.79 ~ 7.47 ppm belongs to H on the benzene ring, and the peaks at 3.47 and 2.65 ppm belong to H on the oxygen and nitrogen of triethanolamine, respectively, which indicates that the target luminescent flame retardant NEDP is successfully synthesized; (b) is a Fourier transform infrared spectrum of the luminescent flame retardant (NEDP), triethanolamine (TEOA) and diphenylphosphonyl chloride (DPC). From the Fourier transform infrared spectrum of triethanolamine, 2885 cm -1 The absorption peak at 3321cm belongs to CH -1 The absorption peak at 3060 belongs to the stretching vibration of NH and -OH, while the absorption peak of diphenylphosphonyl chloride at 3060 -1 ,1438 -1 ,1231 -1 and 616cm -1 The peaks at 934 cm-1 are attributed to the stretching vibrations of CH, P-Ph, P=O, and P-Cl, respectively. By comparing the Fourier transform infrared spectra of -OH and P-Cl, it can be concluded that the peaks of -OH and P-Cl disappear, while the peaks at 934 cm-1 are -1 A new PO peak was generated at , which proved that triethanolamine and diphenylphosphonyl chloride successfully synthesized the target product luminescent flame retardant (NEDP).
[0033] like Figure 2 , is the infrared spectrum of the transparent polyurethane material prepared in Examples 1-4 of the present invention. It can be seen from the figure that the synthesized luminescent flame retardant successfully enters the polyurethane matrix, and the 2260 cm -1 The -NCO absorption peak near the -NCO group disappears, indicating that the -NCO group fully reacts with the -OH group. The stretching vibration peaks of the saturated CH2 in the molecular chain appear at 2939-1 ,2924 -1 and 2856 cm -1 Nearby, under the influence of NH, the characteristic absorption peak of CO in polyurethane shifted slightly to a lower wavelength of 1728 cm -1 Compared with pure polyurethane (TPU), the characteristic peaks of NEDP in the polyurethanes prepared in Examples 1-4 of the present invention are located at 1222 cm -1 (P=O) and 955 cm -1 (PO) and 3343 cm -1 (NH), where 1222 cm -1 (P=O) and 955 cm -1 The characteristic peak at (PO) is the most obvious. The results show that the luminescent flame retardant NEDP is successfully introduced into the polyurethane structure, and polyurethane materials with different NEDP contents are successfully prepared.
[0034] like Figure 3 and Figure 4 It can be seen that the polyurethane materials prepared in Examples 1-4 of the present invention have excellent flame retardant properties and mechanical properties. Figure 3 As can be seen from (a), compared with pure polyurethane without adding luminescent flame retardant, the combustion condition and melting drop phenomenon of the polyurethane material prepared by the present invention are greatly improved, the mass loss of the polyurethane material is reduced, and the limiting oxygen index LOI is increased from 17.8 to 30.3.
[0035] Figure 3 (b) is the vertical combustion test of pure polyurethane and different samples of Example 1. It can be seen that the pure polyurethane sample has obvious combustion phenomenon and serious molten drop phenomenon in the vertical combustion test. The dripping droplets ignited the absorbent cotton below, and the secondary ignition not only ignited the absorbent cotton, but also almost burned out the sample strip. After adding the luminous flame retardant, the burning phenomenon of the sample strip was greatly alleviated, and the molten drop phenomenon was also greatly improved. From the pure polyurethane elastomer easily igniting the absorbent cotton below to the ignition time of the absorbent cotton gradually extending, until after adding 9 mol of luminous flame retardant, the absorbent cotton could not be ignited at all, and after the secondary ignition, it was found that the slight molten drop still could not ignite the absorbent cotton below, and the best flame retardant grade was obtained, and the UL-94 flame retardant grade was upgraded from no grade to V-0 grade. Figure 3 It can also be seen in (c) that the flame retardancy of polyurethane is greatly improved after the introduction of NEDP compared to pure polyurethane. The high efficiency flame retardant performance of polyurethane materials is mainly due to the synergistic flame retardant effect of the luminescent flame retardant in both the gas phase and the condensed phase, thus achieving better flame retardant properties.
[0036] In addition, if Figure 4Compared with the pure polyurethane material without adding the luminescent flame retardant, the tensile strength of the polyurethane materials prepared in Examples 1-4 of the present invention is still maintained above 25 MPa. Specifically, the stresses of Examples 1-4 are 27.9 MPa, 28 MPa, 27.81 MPa, and 26.8 MPa, respectively, and the strains are 1022%, 1002%, 997%, and 1466%, respectively. This shows that the polyurethane material after adding the luminescent flame retardant still maintains good mechanical properties, thereby ensuring the needs in practical applications.
[0037] like Figure 5 As can be seen from the figure, the light transmittance of the polyurethane materials prepared in Examples 1-4 of the present invention is maintained at more than 80%, while the light transmittance of the polyurethane materials prepared in Comparative Examples 1-3 fluctuates between 60-78%, which is a large gap compared with the light transmittance of the polyurethane materials prepared in the examples. This shows that the polyurethane materials prepared in Examples 1-4 of the present invention have high light transmittance and can be used as light transfer films on flexible solar cells, thereby improving the photoelectric conversion efficiency of flexible solar cells.
[0038] like Figure 6 , which are scanning electron microscope characterization images of the carbon layer of the polyurethane material prepared in Example 1 of the present invention and the pure polyurethane material after combustion, from Figure 6 As can be seen from (a1) and (b1), the carbon layer of pure polyurethane is thin and has pore defects, which is very easy to collapse. In addition, the defects will also lead to continuous contact with the combustible gas and continuous heat transfer, thus causing continuous combustion. Figure 6 (a2) and (b2) show that after the addition of the luminescent flame retardant, the nitride and phosphoric acid products promote the formation of ammonium phosphate, which covers the surface of the polyurethane matrix and forms a dense and smooth carbon layer, making the carbon layer thicker, achieving the effect of physically blocking the combustible gas in the air and blocking heat transfer, thereby achieving a better flame retardant effect.
[0039] Figure 7 The recyclability test of the polyurethane material prepared in Example 1 of the present invention is conducted. During the recycling process, the polyurethane material is first cut into small pieces, and these pieces are then reshaped into dumbbell-shaped specimens, hot-pressed at 120°C and 5 MPa for 1 h, and then gradually cooled to 25-30°C. The cooled specimens are kept at this temperature for 24 h to achieve structural stability, during which effective reintegration of the fragments can be observed. The performance comparison evaluation conducted by stress-strain curve analysis shows that the mechanical properties of the original polyurethane specimen and the reshaped polyurethane specimen are almost exactly the same. This significant performance retention can prove that the polyurethane material prepared by the present invention is a recyclable material that can be reused and meets the requirements of contemporary ecological protection and low-carbon goals.
[0040] like Figure 8 , which is a characterization diagram of the luminescent performance of the polyurethane materials prepared in Examples 1-4 of the present invention. It can be seen from the figure that each material shows obvious fluorescence intensity at an excitation wavelength of 365 nm, and it continues to increase with the addition of the luminescent flame retardant. The polyurethane material after adding the luminescent flame retardant absorbs the incident 365 nm ultraviolet light and converts it into visible blue light above 400 nm, and the fluorescence intensity is strong. Since the flexible solar cell panel has a very low absorption utilization rate for ultraviolet light below 400 nm, and the visible light has a high power generation efficiency, the photoelectric conversion efficiency after conversion to visible light becomes higher, so that it can be used in flexible solar cells to increase the photoelectric conversion efficiency of solar cells.
[0041] In addition, the polyurethane materials prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention and pure polyurethane were used as light transfer films on flexible solar panels. The photoelectric conversion efficiency was tested by inputting light power of the same intensity on the flexible solar panels. The specific data are shown in the following table:
[0042] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a flame retardant, luminous and recyclable transparent polyurethane material, characterized in that: Follow the steps below in order: S1. Preparation of luminescent flame retardant Triethylamine was added to 50 mL of anhydrous tetrahydrofuran at 0°C, and triethanolamine was added and stirred for 30 min, followed by dropwise addition of diphenylphosphonyl chloride and stirring for 3-5 h, the reaction system was quenched with water, 100 mL of water and 100 mL of ethyl acetate were added for extraction, the obtained organic phase was washed 2-4 times with 100 mL of deionized water and 100 mL of saturated brine, 5 g of anhydrous sodium sulfate was added for drying, filtration, concentration under reduced pressure and purification by column chromatography to obtain a luminescent flame retardant; S2. Preparation of transparent polyurethane material Add polyether polyol into a three-necked flask and heat it to 120°C, then evacuate the glass container and fill it with argon, cool the system to 80°C, add isocyanate and stir for 1 h, then lower the temperature to 55°C, add luminescent flame retardant and chain extender, stir for 1-2 min, add 0.6 mL triethylamine to obtain a polymer emulsion, pour it into a polytetrafluoroethylene mold, react and cure in an 80°C oven for 48 h to obtain a transparent polyurethane material.
2. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S1, the molar ratio of triethylamine, triethanolamine and diphenylphosphonyl chloride is 5:1:
3.
3. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S1, the dropping rate of diphenylphosphonyl chloride is 0.5-0.6 mL / min.
4. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S2, the molecular weight of the polyether polyol is 1000-3000.
5. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S2, the isocyanate is any one of hexamethylene diisocyanate, isophorone diisocyanate, methylcyclohexyl diisocyanate, dicyclohexyl methylene diisocyanate, xylylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and dimer acid diisocyanate.
6. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S2, the molar ratio of the polyether polyol to the isocyanate, the luminescent flame retardant, and the chain extender is 10:20:(3-12):
10.
7. The method for preparing a flame retardant, luminescent and recyclable transparent polyurethane material according to claim 1, characterized in that: In step S2, the chain extender is prepared by adding 0.9 g 1,4-butanediol into 2 mL N,N-dimethylformamide and stirring evenly.
8. A method for preparing a flame retardant, luminous and recyclable transparent polyurethane material according to any one of claims 1 to 3, characterized in that: In step S1, the structural formula of the luminescent flame retardant prepared is: 。 9. A method for preparing a flame retardant, luminous and recyclable transparent polyurethane material according to any one of claims 1 to 7, characterized in that: The prepared transparent polyurethane material can be used as a light transfer film on flexible solar cells.
Citation Information
Patent Citations
Polysiloxane fire retardant containing nitrogen, phosphorus and silicon, and preparation method thereof
CN106700081A
Photosensitive resin, photosensitive resin composition, cured product, and color filter
CN115113481A
Linear phosphoramide oligomer flame retardant, preparation method thereof and application of linear phosphoramide oligomer flame retardant in thermoplastic polyurethane elastomer
CN117757084A
Preparation method of non-additive nitrogen-phosphorus-cerium synergistic flame-retardant polyurethane elastomer
CN119331214A
Use of carboxy phosphane oxide photoinitiator novel cpds. - in high energy irradiation of polymerisable moulding compsns. coatings or printing inks, for ultraviolet curable compsns.
DE4025386A1
Cited By
Method for preparing polyurethane material based on fluorescent flame retardant
CN120329512A
Preparation method of transparent polyurethane material with flame retardance, high strength and recoverability
CN121574339A
A method for preparing a transparent polyurethane material with flame retardancy, high strength and recyclability
CN121574339B